Results for patients with sarcoma not otherwise specified and other diagnoses than Ewing sarcoma treated according to the Euro‐EWING 99 trial. Issue 10 (24th April 2017) - Frank, Judith Amalie; Ranft, Andreas; Paulussen, Michael; Juergens, Heribert; Kruseova, Jarmila; Bauer, Sebastian; Niggli, Felix; Reichardt, Peter; Dirksen, Uta
Abstract: Background: Euro‐EWING 99 trial of the European Ewing tumor Working Initiative of National Groups (EE99) was an international phase III study in patients with Ewing sarcoma. The German Society of Pediatric Oncology and Hematology (GPOH) data center registered and followed patients with other diagnoses than Ewing sarcoma who were treated according to the EE99 protocol in an additional non‐Ewing database. Procedure: Data of 27 patients with other diagnoses than Ewing sarcoma treated according to the EE99 protocol were analyzed. Patients had miscellaneous histologic diagnoses, the majority were diagnosed with sarcoma not otherwise specified (NOS) arising in bone and soft tissue (63%). Results: The median age at diagnosis was 16.9 years (range 4.5–41.4). Localized disease was diagnosed in 61.5% of the patients and 38.5% had distant metastases at time of primary diagnosis. The median follow‐up time was 3.7 years (range 0.5–9.5). Patients with localized disease showed a 3‐year event‐free survival (EFS) of 68%, compared to 3‐year EFS of 20% in patients with metastases ( P = 0.042). Three‐year EFS for patients with sarcoma NOS was 52%, patients with localized and metastatic disease showed 3‐year EFS of 66 and 20%, respectively. Conclusion: EFS in patients with other diagnoses than Ewing sarcoma treated according to EE99 was significantly higher in patients with localized than metastatic disease. Sarcomas of soft tissue and bone that cannot be classified to current diagnostic categories constitute a therapeutic challenge.